The effect of hydrogen on the electronic properties of CVD diamond films - Looi, H; Whitfield, MD; Foord, J; Jackman, R (1999)
Thin film diamond, grown by chemical vapour deposition, have been found to display p-type surface conductivity. No bulk impurity is added to the films; the p-type characteristics of the undoped diamond are thought to be due to a surface or near surface hydrogenated layer. Carrier concentrations within the range 1017-1019 cm-3 have been measured; control over the carrier concentration can be achieved by annealing the 'as-grown' films in air. For a given annealing temperature a stable carrier concentration arises. The Hall carrier mobility has been measured and a value of >70 cm2/Vs has been found for a film with a carrier concentration of ∼ 5 × 1017 cm-3. the highest reported for polycrystalline thin film diamond and equivalent to boron doped single crystal diamond, I-V characteristics for Al-based Schottky diodes are good (ideality factor 1.1) and show no breakdown at reverse bias levels greater than 100 V, suggesting this form of diamond is well suited to electronic applications. © 1999 Elsevier Science S.A. All rights reserved.